The impact of COVID-19 on diet quality, food security and nutrition in low and middle income countries: A systematic review of the evidence. Issue 12 (December 2022) - Picchioni, Fiorella; Goulao, Luis F.; Roberfroid, Dominique
Summary: Background & aims: The current global pandemic of Coronavirus (COVID-19), and measures adopted to reduce its spread, threaten the nutritional status of populations in Low- and middle-income countries (LMICs). Documenting how the COVID-19 affects diets, nutrition and food security can help generating evidence-informed recommendations for mitigating interventions and policies. Methods: We carried out a systematic literature review. A structured search strategy was applied in MEDLINE (Pubmed®), EMBASE®, Scopus® and Web of Science®. Grey literature was retrieved by screening a pre-set list of institutions involved in monitoring the impact of the COVID-19 pandemic on nutrition and food security. The first search was done on 20th August 2020, and updated in mid-November 2020 and mid-January 2021. All research steps were described as recommended in the PRISMA statement. Results: Out of the 2085 references identified, thirty-five primary studies were included. In spite of their heterogeneity, studies converge to demonstrate a detrimental effect of COVID-19 pandemic and associated containment measures on diet quality and food insecurity. One of the major direct effects of COVID-19 on food and nutrition outcomes has been through its impact on employment, income generating activities and associated purchasing power. Other channels of impact, such as physical access, availability and affordability of food provided a heterogeneous picture and were assessed via binary and often simplistic questions. The impacts of COVID-19 on food systems and diets manifested with various intensity degrees, duration and in different forms. Factors contributing to these variations between and within countries were: 1) timing, duration and stringency of national COVID-19 restriction measures and policies to mitigate their adverse impacts; 2) context specific food value chain responses to domestic and international containment measures; 3) differentiated impacts of restriction measures on different groups, along lines of gender, age, socio-economic status and employment conditions. Shorter value chains and traditional smallholder farms were somewhat more resilient in the face of COVID-19 pandemic. Additionally, the impact of the pandemic has been particularly adverse on women, individuals with a low socio-economic status, informal workers and young adults that relied on daily wages. Finally, there were heterogeneous government responses to curb the virus and to mitigate the damaging effects of the pandemic. It has been demonstrated that existing and well-functioning social protection programmes and public distribution of food can buffer the adverse effects on food insecurity. But social safety nets cannot be effective on their own and there is a need for broader food systems interventions and investments to support sustainable and inclusive food systems to holistically achieve food and nutrition security. Conclusion: The current economic and heath crisis impacted diet quality and food security. This raises concerns about long term impacts on access to and affordability of nutrient-rich, healthy diets and their health implications. Women and individuals with a low socio-economic are likely to be the most at risk of food insecurity. Social safety nets can be effective to protect them and must be urgently implemented. We advocate for improved data collection to identify vulnerable groups and measure how interventions are successful in protecting them.